Seasonal Variation of Physico-chemical Properties and Fertility of Soils under Different Land Uses in Nagaland - Bordoloi, Jurisandhya; Sharma, Y. K. (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted in the Department of Agricultural Chemistry and Soil Science, SASRD, Nagaland University during 2018 to evaluate the seasonal variation of soil physico-chemical properties under forest (natural), pineapple and paddy (low land) land use systems (LUS) of Medziphema block, Dimapur, Nagaland. 432 geo-referenced composite soil samples were collected during pre-monsoon, monsoon and post-monsoon seasons from surface and sub-surface soil. pH of soils under paddy LUS was found highest (4.95) followed by forest (4.84) and pineapple (4.65) LUS. Significantly minimum values of BD was recorded in forest LUS (1.17 and 1.20 Mg m-3) followed by higher BD (1.21 and 1.25 Mg m-3) in pineapple and maximum in paddy LUS (1.34 and 1.37 Mg m-3) during post-monsoon season at surface and sub-surface soil respectively. Forest LUS recorded maximum average content of organic carbon (16.72 g kg-1). Available nitrogen, available phosphorus, exchangeable calcium and magnesium content was also found maximum in soils of forest LUS. Significant positive correlation among soil fertility parameters were obtained in different seasons. Results of the investigation revealed that the pineapple LUS in the study area can be considered as a sustainable LUS owing to its comparable soil physico-chemical properties with the forest LUS. However, there is need for large scale adoption of location specific soil management practices for sustainable production and management of soil health in order to counteract deterioration of soil fertility under traditionally practiced low land paddy LUS.